Geometric series are series of the form
∑
k
=
0
∞
q
k
{\displaystyle \sum _{k=0}^{\infty }q^{k}}
. They are important within several proofs in real analysis. In particular, they are crucial for proving convergence or divergence of other series. We will derive some criteria using them, e.g. the ratio or the root criterion.
A video explaining the geometric series (in German).(YouTube-Video by the channel Quatematik )
We recall the geometric sum formula for partial sums of the geometric series. If you would like to know more about the geometric sum formula, take a look at the article „Geometrische Summenformel“ . The sum formula is proven there via induction. The proof of the sum formula reads as follows:
Proof (Geometrische Summenformel)
We have
∑
k
=
0
n
q
k
=
1
+
q
+
q
2
+
⋯
+
q
n
↓
multiply both side by
q
⟹
q
⋅
∑
k
=
0
n
q
k
=
q
+
q
2
+
q
3
+
⋯
+
q
n
+
1
↓
subtract second from first equation
⟹
∑
k
=
0
n
q
k
−
q
⋅
∑
k
=
0
n
q
k
=
(
1
+
q
+
⋯
+
q
n
)
−
(
q
+
q
2
+
⋯
+
q
n
+
1
)
=
1
−
q
n
+
1
↓
factor out
∑
k
=
0
n
q
k
⟹
(
1
−
q
)
⋅
∑
k
=
0
n
q
k
=
1
−
q
n
+
1
↓
⋅
1
1
−
q
, since
q
≠
1
⟹
∑
k
=
0
n
q
k
=
1
−
q
n
+
1
1
−
q
{\displaystyle {\begin{aligned}\sum _{k=0}^{n}q^{k}&=\ 1+q+q^{2}+\dotsb +q^{n}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{multiply both side by }}q\right.}\\[0.5em]\implies \ q\cdot \sum _{k=0}^{n}q^{k}&=\ q+q^{2}+q^{3}+\dotsb +q^{n+1}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{subtract second from first equation}}\right.}\\[0.5em]\implies \ \sum _{k=0}^{n}q^{k}-q\cdot \sum _{k=0}^{n}q^{k}&=\ (1+q+\dotsb +q^{n})-(q+q^{2}+\dotsb +q^{n+1})\\[0.5em]&=1-q^{n+1}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{factor out }}\sum _{k=0}^{n}q^{k}\right.}\\[0.5em]\implies \ (1-q)\cdot \sum _{k=0}^{n}q^{k}&=\ 1-q^{n+1}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {}\cdot {\frac {1}{1-q}}{\text{, since }}q\neq 1\right.}\\[0.5em]\implies \ \sum _{k=0}^{n}q^{k}&=\ {\frac {1-q^{n+1}}{1-q}}\\[0.5em]\end{aligned}}}
A (German) song about the geometric series (Youtube-Video by DorFuchs )
The geometric series
∑
k
=
0
∞
r
k
{\displaystyle \sum _{k=0}^{\infty }r^{k}}
converges for
r
=
1
2
{\displaystyle r={\tfrac {1}{2}}}
,
r
=
1
3
{\displaystyle r={\tfrac {1}{3}}}
or
r
=
1
4
{\displaystyle r={\tfrac {1}{4}}}
.
We consider two cases:
|
q
|
<
1
{\displaystyle |q|<1}
and
|
q
|
≥
1
{\displaystyle |q|\geq 1}
.
We consider the geometric series
∑
k
=
0
∞
q
k
{\displaystyle \sum _{k=0}^{\infty }q^{k}}
for any
|
q
|
<
1
{\displaystyle |q|<1}
, which especially means
q
≠
1
{\displaystyle q\neq 1}
. The sum formula above applies to the partial sums in that case:
∑
k
=
0
∞
q
k
=
(
∑
k
=
0
n
q
k
)
n
∈
N
↓
geometric sum formula
(
q
≠
1
)
=
(
1
−
q
n
+
1
1
−
q
)
n
∈
N
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }q^{k}&=\left(\sum _{k=0}^{n}q^{k}\right)_{n\in \mathbb {N} }\\[1em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric sum formula }}(q\neq 1)\right.}\\[1em]&=\left({\frac {1-q^{n+1}}{1-q}}\right)_{n\in \mathbb {N} }\end{aligned}}}
So the geometric series converges if and only if the sequence of partial sums
(
1
−
q
n
+
1
1
−
q
)
n
∈
N
{\displaystyle \left({\tfrac {1-q^{n+1}}{1-q}}\right)_{n\in \mathbb {N} }}
converges. This is the case if and only if
(
q
n
)
n
∈
N
{\displaystyle \left(q^{n}\right)_{n\in \mathbb {N} }}
converges. We know that
(
q
n
)
n
∈
N
{\displaystyle \left(q^{n}\right)_{n\in \mathbb {N} }}
converges to
0
{\displaystyle 0}
if and only if
|
q
|
<
1
{\displaystyle |q|<1}
and it converges to
1
{\displaystyle 1}
, if and only if
q
=
1
{\displaystyle q=1}
. In this section, we only care about the first case of convergence:
Now, let us determine its limit:
∑
k
=
0
∞
q
k
=
lim
n
→
∞
∑
k
=
0
n
q
k
=
lim
n
→
∞
1
−
q
n
+
1
1
−
q
↓
limit theorems
=
1
−
lim
n
→
∞
q
n
+
1
1
−
q
↓
|
q
|
<
1
=
1
−
0
1
−
q
=
1
1
−
q
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }q^{k}&=\lim _{n\to \infty }\sum _{k=0}^{n}q^{k}\\[0.3em]&=\lim _{n\to \infty }{\frac {1-q^{n+1}}{1-q}}\\[0.3em]&{\color {OliveGreen}\left\downarrow \ {\text{limit theorems}}\right.}\\[0.3em]&={\frac {1-\lim _{n\to \infty }q^{n+1}}{1-q}}\\[0.3em]&{\color {OliveGreen}\left\downarrow \ |q|<1\right.}\\[0.3em]&={\frac {1-0}{1-q}}\\[0.3em]&={\frac {1}{1-q}}\end{aligned}}}
Alternatively, convergence for
|
q
|
<
1
{\displaystyle |q|<1}
can be shown directly, using the definition.
Math for Non-Geeks: Template:Aufgabe
For
|
q
|
≥
1
{\displaystyle |q|\geq 1}
, we have for all
k
∈
N
0
{\displaystyle k\in \mathbb {N} _{0}}
, that
|
q
k
|
≥
1
{\displaystyle \left|q^{k}\right|\geq 1}
. Therefore, the sequence
(
q
k
)
k
∈
N
0
{\displaystyle \left(q^{k}\right)_{k\in \mathbb {N} _{0}}}
cannot converge to 0. So teh series
∑
k
=
0
∞
q
k
{\displaystyle \sum _{k=0}^{\infty }q^{k}}
must diverge (this argument is called term test and will be considered in detail, later)
The divergence becomes particularly obvious, if
q
{\displaystyle q}
is positive, e.g. for
q
≥
1
{\displaystyle q\geq 1}
.
In this case, for all
k
∈
N
{\displaystyle k\in \mathbb {N} }
, we have
q
k
≥
1
{\displaystyle q^{k}\geq 1}
and may estimate the partial sums:
∑
k
=
1
n
q
k
≥
∑
k
=
1
n
1
=
n
{\displaystyle \sum _{k=1}^{n}q^{k}\geq \sum _{k=1}^{n}1=n}
So the sequence of partial sums is bounded from below by the sequence
(
n
)
n
∈
N
{\displaystyle (n)_{n\in \mathbb {N} }}
, which in turn diverges to
+
∞
{\displaystyle +\infty }
. So the series
∑
k
=
0
∞
q
k
{\displaystyle \sum _{k=0}^{\infty }q^{k}}
must diverge, as well.
We have learned: for
|
q
|
>
1
{\displaystyle |q|>1}
,
q
=
−
1
{\displaystyle q=-1}
and
q
=
1
{\displaystyle q=1}
, the geometric series diverges. These three cases can be concluded into one case
|
q
|
≥
1
{\displaystyle |q|\geq 1}
. However, if
|
q
|
<
1
{\displaystyle |q|<1}
, then the geometric series converges to
1
1
−
q
{\displaystyle {\tfrac {1}{1-q}}}
:
Theorem (geometric series)
The geometric series
∑
k
=
0
∞
q
k
{\displaystyle \sum _{k=0}^{\infty }q^{k}}
converges if and only if
|
q
|
<
1
{\displaystyle |q|<1}
. In that case, the limit is
1
1
−
q
{\displaystyle {\tfrac {1}{1-q}}}
, or written in shorthand notation:
∑
k
=
0
∞
q
k
=
{
1
1
−
q
;
|
q
|
<
1
diverges
;
|
q
|
≥
1
{\displaystyle \sum _{k=0}^{\infty }q^{k}={\begin{cases}{\frac {1}{1-q}}&;|q|<1\\{\text{diverges}}&;|q|\geq 1\end{cases}}}
Example (geometric series)
For
q
=
1
2
{\displaystyle q={\tfrac {1}{2}}}
,
q
=
−
1
2
{\displaystyle q=-{\tfrac {1}{2}}}
and
q
=
2
{\displaystyle q=2}
there is
∑
k
=
0
∞
(
1
2
)
k
=
1
+
1
2
+
1
4
+
1
8
+
1
16
+
…
=
1
1
−
1
2
=
1
1
2
=
2
∑
k
=
0
∞
(
−
1
2
)
k
=
1
−
1
2
+
1
4
−
1
8
+
1
16
−
…
=
1
1
+
1
2
=
1
3
2
=
2
3
∑
k
=
0
∞
2
k
=
1
+
2
+
4
+
8
+
16
+
…
diverges to
+
∞
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }\left({\frac {1}{2}}\right)^{k}&=1+{\frac {1}{2}}+{\frac {1}{4}}+{\frac {1}{8}}+{\frac {1}{16}}+\ldots ={\frac {1}{1-{\frac {1}{2}}}}={\frac {1}{\frac {1}{2}}}=2\\[1em]\sum _{k=0}^{\infty }\left(-{\frac {1}{2}}\right)^{k}&=1-{\frac {1}{2}}+{\frac {1}{4}}-{\frac {1}{8}}+{\frac {1}{16}}-\ldots ={\frac {1}{1+{\frac {1}{2}}}}={\frac {1}{\frac {3}{2}}}={\frac {2}{3}}\\[1em]\sum _{k=0}^{\infty }2^{k}&=1+2+4+8+16+\ldots \ {\text{ diverges to }}+\infty \end{aligned}}}
Solution (problems: geometric series)
Solution sub-exercise 1:
∑
k
=
0
∞
1
3
k
=
∑
k
=
0
∞
1
k
3
k
=
∑
k
=
0
∞
(
1
3
)
k
↓
∑
k
=
0
∞
(
1
3
)
k
=
1
1
−
1
3
=
1
2
3
=
3
2
=
3
2
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {1}{3^{k}}}&=\sum _{k=0}^{\infty }{\frac {1^{k}}{3^{k}}}\\[0.5em]&=\sum _{k=0}^{\infty }\left({\frac {1}{3}}\right)^{k}\\[0.5em]&\quad {\color {OliveGreen}\left\downarrow \ \sum _{k=0}^{\infty }\left({\frac {1}{3}}\right)^{k}={\frac {1}{1-{\frac {1}{3}}}}={\frac {1}{\frac {2}{3}}}={\frac {3}{2}}\right.}\\[0.5em]&={\frac {3}{2}}\end{aligned}}}
Solution sub-exercise 2:
∑
k
=
0
∞
2
k
3
k
=
∑
k
=
0
∞
(
2
3
)
k
↓
∑
k
=
0
∞
(
2
3
)
k
=
1
1
−
2
3
=
1
1
3
=
3
=
3
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {2^{k}}{3^{k}}}&=\sum _{k=0}^{\infty }\left({\frac {2}{3}}\right)^{k}\\[0.5em]&\quad {\color {OliveGreen}\left\downarrow \ \sum _{k=0}^{\infty }\left({\frac {2}{3}}\right)^{k}={\frac {1}{1-{\frac {2}{3}}}}={\frac {1}{\frac {1}{3}}}=3\right.}\\[0.5em]&=3\end{aligned}}}
Solution sub-exercise 3:
∑
k
=
0
∞
(
−
2
)
k
3
k
=
∑
k
=
0
∞
(
−
2
3
)
k
↓
∑
k
=
0
∞
(
−
2
3
)
k
=
1
1
−
(
−
2
3
)
=
1
1
+
2
3
=
1
5
3
=
3
5
=
3
5
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {(-2)^{k}}{3^{k}}}&=\sum _{k=0}^{\infty }\left(-{\frac {2}{3}}\right)^{k}\\[0.5em]&\quad {\color {OliveGreen}\left\downarrow \ \sum _{k=0}^{\infty }\left(-{\frac {2}{3}}\right)^{k}={\frac {1}{1-(-{\frac {2}{3}})}}={\frac {1}{1+{\frac {2}{3}}}}={\frac {1}{\frac {5}{3}}}={\frac {3}{5}}\right.}\\[0.5em]&={\frac {3}{5}}\end{aligned}}}
Solution sub-exercise 5:
This series starts with
k
=
4
{\displaystyle k=4}
. We perform an index shift to get it starting with
k
=
0
{\displaystyle k=0}
:
∑
k
=
4
∞
1
3
k
−
2
=
index
shift
(
∑
k
=
2
∞
1
3
k
)
=
(
∑
k
=
0
∞
1
3
k
)
−
1
3
0
−
1
3
1
=
(
∑
k
=
0
∞
(
1
3
)
k
)
−
1
−
1
3
↓
∑
k
=
0
∞
(
1
3
)
k
=
1
1
−
1
3
=
3
2
=
3
2
−
1
−
1
3
=
1
2
−
1
3
=
3
6
−
2
6
=
1
6
{\displaystyle {\begin{aligned}\sum _{k=4}^{\infty }{\frac {1}{3^{k-2}}}&{\underset {\text{shift}}{\overset {\text{index}}{=}}}\left(\sum _{k=2}^{\infty }{\frac {1}{3^{k}}}\right)\\[0.5em]&=\left(\sum _{k=0}^{\infty }{\frac {1}{3^{k}}}\right)-{\frac {1}{3^{0}}}-{\frac {1}{3^{1}}}\\[0.5em]&=\left(\sum _{k=0}^{\infty }\left({\frac {1}{3}}\right)^{k}\right)-1-{\frac {1}{3}}\\[0.5em]&\quad {\color {OliveGreen}\left\downarrow \ \sum _{k=0}^{\infty }\left({\frac {1}{3}}\right)^{k}={\frac {1}{1-{\frac {1}{3}}}}={\frac {3}{2}}\right.}\\[0.5em]&={\frac {3}{2}}-1-{\frac {1}{3}}\\[0.5em]&={\frac {1}{2}}-{\frac {1}{3}}\\[0.5em]&={\frac {3}{6}}-{\frac {2}{6}}={\frac {1}{6}}\end{aligned}}}
Solution (geometric series with special
q
{\displaystyle q}
)
Solution sub-exercise 1:
∑
k
=
0
∞
1
N
k
=
∑
k
=
0
∞
(
1
N
)
k
↓
geometric series with
q
=
1
N
=
1
1
−
1
N
=
1
N
−
1
N
=
N
N
−
1
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {1}{N^{k}}}&=\sum _{k=0}^{\infty }\left({\frac {1}{N}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric series with }}q={\frac {1}{N}}\right.}\\[0.5em]&={\frac {1}{1-{\frac {1}{N}}}}={\frac {1}{\frac {N-1}{N}}}={\frac {N}{N-1}}\end{aligned}}}
and
∑
k
=
0
∞
(
−
1
)
k
N
k
=
∑
k
=
0
∞
(
−
1
N
)
k
↓
geometric series with
q
=
−
1
N
=
1
1
+
1
N
=
1
N
+
1
N
=
N
N
+
1
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {(-1)^{k}}{N^{k}}}&=\sum _{k=0}^{\infty }\left(-{\frac {1}{N}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric series with }}q=-{\frac {1}{N}}\right.}\\[0.5em]&={\frac {1}{1+{\frac {1}{N}}}}={\frac {1}{\frac {N+1}{N}}}={\frac {N}{N+1}}\end{aligned}}}
Solution sub-exercise 2:
∑
k
=
0
∞
M
k
(
M
+
1
)
k
=
∑
k
=
0
∞
(
M
M
+
1
)
k
↓
geometric series with
q
=
M
M
+
1
=
1
1
−
M
M
+
1
=
1
1
M
+
1
=
M
+
1
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {M^{k}}{(M+1)^{k}}}&=\sum _{k=0}^{\infty }\left({\frac {M}{M+1}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric series with }}q={\frac {M}{M+1}}\right.}\\[0.5em]&={\frac {1}{1-{\frac {M}{M+1}}}}={\frac {1}{\frac {1}{M+1}}}=M+1\end{aligned}}}
and
∑
k
=
0
∞
(
−
1
)
k
M
k
(
M
+
1
)
k
=
∑
k
=
0
∞
(
−
M
M
+
1
)
k
↓
geometric series with
q
=
−
M
M
+
1
=
1
1
+
M
M
+
1
=
1
2
M
+
1
M
+
1
=
M
+
1
2
M
+
1
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }(-1)^{k}{\frac {M^{k}}{(M+1)^{k}}}&=\sum _{k=0}^{\infty }\left(-{\frac {M}{M+1}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric series with }}q=-{\frac {M}{M+1}}\right.}\\[0.5em]&={\frac {1}{1+{\frac {M}{M+1}}}}={\frac {1}{\frac {2M+1}{M+1}}}={\frac {M+1}{2M+1}}\end{aligned}}}
Solution sub-exercise 3:
∑
k
=
0
∞
M
k
N
k
=
∑
k
=
0
∞
(
M
N
)
k
↓
geometric series with
q
=
M
N
=
1
1
−
M
N
=
1
N
−
M
N
=
N
N
−
M
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {M^{k}}{N^{k}}}&=\sum _{k=0}^{\infty }\left({\frac {M}{N}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric series with }}q={\frac {M}{N}}\right.}\\[0.5em]&={\frac {1}{1-{\frac {M}{N}}}}={\frac {1}{\frac {N-M}{N}}}={\frac {N}{N-M}}\end{aligned}}}
and
∑
k
=
0
∞
(
−
1
)
k
M
k
N
k
=
∑
k
=
0
∞
(
−
M
N
)
k
↓
geometric series with
q
=
−
M
N
=
1
1
+
M
N
=
1
N
+
M
N
=
N
N
+
M
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }(-1)^{k}{\frac {M^{k}}{N^{k}}}&=\sum _{k=0}^{\infty }\left(-{\frac {M}{N}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric series with }}q=-{\frac {M}{N}}\right.}\\[0.5em]&={\frac {1}{1+{\frac {M}{N}}}}={\frac {1}{\frac {N+M}{N}}}={\frac {N}{N+M}}\end{aligned}}}
Solution (index shifting)
Solution sub-exercise 1:
∑
k
=
1
∞
q
k
=
(
∑
k
=
0
∞
q
k
)
−
q
0
=
(
∑
k
=
0
∞
q
k
)
−
1
↓
∑
k
=
0
∞
q
k
=
1
1
−
q
=
1
1
−
q
−
1
=
1
1
−
q
−
1
−
q
1
−
q
=
1
−
(
1
−
q
)
1
−
q
=
q
1
−
q
{\displaystyle {\begin{aligned}\sum _{k=1}^{\infty }q^{k}&=\left(\sum _{k=0}^{\infty }q^{k}\right)-q^{0}\\[0.5em]&=\left(\sum _{k=0}^{\infty }q^{k}\right)-1\\[0.5em]&\quad {\color {OliveGreen}\left\downarrow \ \sum _{k=0}^{\infty }q^{k}={\frac {1}{1-q}}\right.}\\[0.5em]&={\frac {1}{1-q}}-1\\[0.5em]&={\frac {1}{1-q}}-{\frac {1-q}{1-q}}\\[0.5em]&={\frac {1-(1-q)}{1-q}}\\[0.5em]&={\frac {q}{1-q}}\end{aligned}}}
Solution sub-exercise 2:
∑
k
=
2
∞
q
k
=
(
∑
k
=
0
∞
q
k
)
−
q
0
−
q
1
=
(
∑
k
=
0
∞
q
k
)
−
1
−
q
↓
∑
k
=
0
∞
q
k
=
1
1
−
q
=
1
1
−
q
−
1
−
q
=
1
1
−
q
−
1
−
q
1
−
q
−
q
(
1
−
q
)
1
−
q
=
1
−
(
1
−
q
)
−
q
(
1
−
q
)
1
−
q
=
1
−
1
+
q
−
q
+
q
2
1
−
q
=
q
2
1
−
q
{\displaystyle {\begin{aligned}\sum _{k=2}^{\infty }q^{k}&=\left(\sum _{k=0}^{\infty }q^{k}\right)-q^{0}-q^{1}\\[0.5em]&=\left(\sum _{k=0}^{\infty }q^{k}\right)-1-q\\[0.5em]&\quad {\color {OliveGreen}\left\downarrow \ \sum _{k=0}^{\infty }q^{k}={\frac {1}{1-q}}\right.}\\[0.5em]&={\frac {1}{1-q}}-1-q\\[0.5em]&={\frac {1}{1-q}}-{\frac {1-q}{1-q}}-{\frac {q(1-q)}{1-q}}\\[0.5em]&={\frac {1-(1-q)-q(1-q)}{1-q}}\\[0.5em]&={\frac {1-1+q-q+q^{2}}{1-q}}\\[0.5em]&={\frac {q^{2}}{1-q}}\end{aligned}}}
Solution sub-exercise 3:
For
|
q
|
<
1
{\displaystyle |q|<1}
and
m
∈
N
{\displaystyle m\in \mathbb {N} }
there is
∑
k
=
m
∞
q
k
=
(
∑
k
=
0
∞
q
k
)
−
∑
k
=
0
m
−
1
q
k
↓
∑
k
=
0
∞
q
k
=
1
1
−
q
v
∑
k
=
0
m
−
1
q
k
=
1
−
q
m
1
−
q
=
1
1
−
q
−
1
−
q
m
1
−
q
=
1
−
(
1
−
q
m
)
1
−
q
=
1
−
1
+
q
m
1
−
q
=
q
m
1
−
q
{\displaystyle {\begin{aligned}\sum _{k=m}^{\infty }q^{k}&=\left(\sum _{k=0}^{\infty }q^{k}\right)-\sum _{k=0}^{m-1}q^{k}\\[0.5em]&\quad {\color {OliveGreen}\left\downarrow \ \sum _{k=0}^{\infty }q^{k}={\frac {1}{1-q}}{\text{ v }}\sum _{k=0}^{m-1}q^{k}={\frac {1-q^{m}}{1-q}}\right.}\\[0.5em]&={\frac {1}{1-q}}-{\frac {1-q^{m}}{1-q}}\\[0.5em]&={\frac {1-(1-q^{m})}{1-q}}\\[0.5em]&={\frac {1-1+q^{m}}{1-q}}\\[0.5em]&={\frac {q^{m}}{1-q}}\end{aligned}}}
Solution (Sequences which relate to the geometric series)
Solution sub-exercise 1:
For all
q
∈
R
{\displaystyle q\in \mathbb {R} }
and
n
∈
N
{\displaystyle n\in \mathbb {N} }
we have to establish
(
1
−
q
)
2
⋅
∑
k
=
0
n
(
k
+
1
)
q
k
=
1
−
(
n
+
2
)
q
n
+
1
+
(
n
+
1
)
q
n
+
2
{\displaystyle (1-q)^{2}\cdot \sum _{k=0}^{n}(k+1)q^{k}=1-(n+2)q^{n+1}+(n+1)q^{n+2}}
the left-hand side is re-arranged as follows:
(
1
−
q
)
2
⋅
∑
k
=
0
n
(
k
+
1
)
q
k
=
(
1
−
2
q
+
q
2
)
⋅
∑
k
=
0
n
(
k
+
1
)
q
k
=
(
1
−
q
−
(
q
−
q
2
)
)
⋅
∑
k
=
0
n
(
k
+
1
)
q
k
=
(
1
−
q
)
⋅
∑
k
=
0
n
(
k
+
1
)
q
k
−
(
q
−
q
2
)
⋅
∑
k
=
0
n
(
k
+
1
)
q
k
=
∑
k
=
0
n
(
k
+
1
)
q
k
−
∑
k
=
0
n
(
k
+
1
)
q
k
+
1
−
[
∑
k
=
0
n
(
k
+
1
)
q
k
+
1
−
∑
k
=
0
n
(
k
+
1
)
q
k
+
2
]
=
1
+
2
q
+
3
q
2
+
4
q
3
+
…
+
n
q
n
−
1
+
(
n
+
1
)
q
n
−
q
−
2
q
2
−
3
q
3
−
…
−
(
n
−
1
)
q
n
−
1
−
n
q
n
−
(
n
+
1
)
q
n
+
1
−
[
q
+
2
q
2
+
3
q
3
+
…
+
(
n
−
1
)
q
n
−
1
+
n
q
n
+
(
n
+
1
)
q
n
+
1
−
q
2
−
2
q
3
−
…
−
(
n
−
2
)
q
n
−
1
−
(
n
−
1
)
q
n
−
n
q
n
+
1
−
(
n
+
1
)
q
n
+
2
]
=
1
+
q
+
q
2
+
q
3
+
…
+
q
n
−
1
+
q
n
−
(
n
+
1
)
q
n
+
1
−
[
q
+
q
2
+
q
3
+
…
+
q
n
−
1
+
q
n
+
q
n
+
1
−
(
n
+
1
)
q
n
+
2
]
↓
telescoping sum
=
1
−
(
n
+
2
)
q
n
+
1
+
(
n
+
1
)
q
n
+
2
{\displaystyle {\begin{aligned}(1-q)^{2}\cdot \sum _{k=0}^{n}(k+1)q^{k}&=(1-2q+q^{2})\cdot \sum _{k=0}^{n}(k+1)q^{k}\\[0.5em]&=(1-q-(q-q^{2}))\cdot \sum _{k=0}^{n}(k+1)q^{k}\\[0.5em]&=(1-q)\cdot \sum _{k=0}^{n}(k+1)q^{k}-(q-q^{2})\cdot \sum _{k=0}^{n}(k+1)q^{k}\\[0.5em]&=\sum _{k=0}^{n}(k+1)q^{k}-\sum _{k=0}^{n}(k+1)q^{k+1}-\left[\sum _{k=0}^{n}(k+1)q^{k+1}-\sum _{k=0}^{n}(k+1)q^{k+2}\right]\\[0.5em]&={\color {OliveGreen}1+2q+3q^{2}+4q^{3}+\ldots +nq^{n-1}+(n+1)q^{n}}\\[0.5em]&\quad {\color {Red}-q-2q^{2}-3q^{3}-\ldots -(n-1)q^{n-1}-nq^{n}-(n+1)q^{n+1}}\\[0.5em]&\quad -\left[{\color {OliveGreen}q+2q^{2}+3q^{3}+\ldots +(n-1)q^{n-1}+nq^{n}+(n+1)q^{n+1}}\right.\\[0.5em]&\qquad \left.{\color {Red}-q^{2}-2q^{3}-\ldots -(n-2)q^{n-1}-(n-1)q^{n}-nq^{n+1}-(n+1)q^{n+2}}\right]\\[0.5em]&=1+q+q^{2}+q^{3}+\ldots +q^{n-1}+q^{n}-(n+1)q^{n+1}\\[0.5em]&\quad -[q+q^{2}+q^{3}+\ldots +q^{n-1}+q^{n}+q^{n+1}-(n+1)q^{n+2}]\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{telescoping sum}}\right.}\\[0.5em]&=1-(n+2)q^{n+1}+(n+1)q^{n+2}\end{aligned}}}
Solution sub-exercise 3:
We re-use the solution to sub-exercise 2 with
q
=
1
2
{\displaystyle q={\tfrac {1}{2}}}
:
∑
k
=
0
∞
k
+
1
2
k
=
∑
k
=
0
∞
(
k
+
1
)
(
1
2
)
k
↓
sub-exercise 2
=
1
(
1
−
1
2
)
2
=
1
(
1
2
)
2
=
1
1
4
=
4
{\displaystyle {\begin{aligned}\sum _{k=0}^{\infty }{\frac {k+1}{2^{k}}}&=\sum _{k=0}^{\infty }(k+1)\left({\frac {1}{2}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{sub-exercise 2}}\right.}\\[0.5em]&={\frac {1}{(1-{\frac {1}{2}})^{2}}}\\[0.5em]&={\frac {1}{({\frac {1}{2}})^{2}}}={\frac {1}{\frac {1}{4}}}=4\end{aligned}}}
The second limit also follows from
q
=
1
2
{\displaystyle q={\tfrac {1}{2}}}
, using an index shift:
∑
k
=
1
∞
k
2
k
=
index-
shift
∑
k
=
0
∞
(
k
+
1
)
(
1
2
)
k
+
1
=
∑
k
=
0
∞
(
k
+
1
)
(
1
2
)
k
1
2
=
1
2
∑
k
=
0
∞
(
k
+
1
)
(
1
2
)
k
↓
sub-exercise 2
=
1
2
1
(
1
−
1
2
)
2
=
1
2
1
1
4
=
4
2
=
2
{\displaystyle {\begin{aligned}\sum _{k=1}^{\infty }{\frac {k}{2^{k}}}&{\underset {\text{shift}}{\overset {\text{index-}}{=}}}\sum _{k=0}^{\infty }(k+1)\left({\frac {1}{2}}\right)^{k+1}\\[0.5em]&=\sum _{k=0}^{\infty }(k+1)\left({\frac {1}{2}}\right)^{k}{\frac {1}{2}}\\[0.5em]&={\frac {1}{2}}\sum _{k=0}^{\infty }(k+1)\left({\frac {1}{2}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{sub-exercise 2}}\right.}\\[0.5em]&={\frac {1}{2}}{\frac {1}{(1-{\frac {1}{2}})^{2}}}\\[0.5em]&={\frac {1}{2}}{\frac {1}{\frac {1}{4}}}={\frac {4}{2}}=2\end{aligned}}}
Solution (Alternative proof to sub-exercise 3)
We may also add and subtract a 1:
∑
k
=
1
∞
k
2
k
=
∑
k
=
0
∞
k
(
1
2
)
k
=
∑
k
=
0
∞
(
k
+
1
−
1
)
(
1
2
)
k
↓
series
∑
k
=
0
∞
(
k
+
1
)
(
1
2
)
k
and
∑
k
=
0
∞
(
1
2
)
k
converge
=
∑
k
=
0
∞
(
k
+
1
)
(
1
2
)
k
−
∑
k
=
0
∞
(
1
2
)
k
↓
sub-exercise 2 with
q
=
1
2
=
1
(
1
−
1
2
)
2
−
∑
k
=
0
∞
(
1
2
)
k
↓
geometric series
=
1
(
1
−
1
2
)
2
−
1
1
−
1
2
=
1
1
4
−
1
1
2
=
4
−
2
=
2
{\displaystyle {\begin{aligned}\sum _{k=1}^{\infty }{\frac {k}{2^{k}}}&=\sum _{k=0}^{\infty }k\left({\frac {1}{2}}\right)^{k}\\[0.5em]&=\sum _{k=0}^{\infty }(k+1-1)\left({\frac {1}{2}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{series }}\sum _{k=0}^{\infty }(k+1)\left({\frac {1}{2}}\right)^{k}{\text{ and }}\sum _{k=0}^{\infty }\left({\frac {1}{2}}\right)^{k}{\text{ converge}}\right.}\\[0.5em]&=\sum _{k=0}^{\infty }(k+1)\left({\frac {1}{2}}\right)^{k}-\sum _{k=0}^{\infty }\left({\frac {1}{2}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{sub-exercise 2 with }}q={\tfrac {1}{2}}\right.}\\[0.5em]&={\frac {1}{(1-{\frac {1}{2}})^{2}}}-\sum _{k=0}^{\infty }\left({\frac {1}{2}}\right)^{k}\\[0.5em]&{\color {OliveGreen}\left\downarrow \ {\text{geometric series}}\right.}\\[0.5em]&={\frac {1}{(1-{\frac {1}{2}})^{2}}}-{\frac {1}{1-{\frac {1}{2}}}}\\[0.5em]&={\frac {1}{\frac {1}{4}}}-{\frac {1}{\frac {1}{2}}}=4-2=2\end{aligned}}}
Hint
Analogously to sub-exercise 3, one may show for every
|
q
|
<
1
{\displaystyle |q|<1}
that:
∑
k
=
1
∞
k
q
k
=
q
(
1
−
q
)
2
{\displaystyle \sum _{k=1}^{\infty }kq^{k}={\frac {q}{(1-q)^{2}}}}
just replace
1
2
{\displaystyle {\tfrac {1}{2}}}
by
q
{\displaystyle q}